Kallfu and Wenutram: two Chilean flaxseed varieties with contrasting mucilage production, composition, and structure - Grant-Grant, Susana; Sanhueza, Dayan; Sepúlveda-Orellana, Pablo; Zúñiga-Pozo, Sebastián; Contreras-Riquelme, J. Sebastián; Alvarez, José M.; Largo-Gosens, Asier; Saez-Aguayo, Susana (Frontiers in Plant Science, 2025)
Seed mucilage, rich in complex polysaccharides, serves diverse functions upon hydration, including soil adhesion, dispersal, and stress protection, making it valuable for food and pharmaceutical applications. Its water-holding capacity aids in food moisture retention, while its emulsifying properties enable various culinary and pharmaceutical uses. Mucilage from flax seeds also offers potential as a bioencapsulation material, with studies exploring its role in drug and probiotic delivery systems targeting the gastrointestinal tract. To investigate differences in mucilage characteristics, we compared two Chilean flaxseed cultivars, Kallfu and Wenutram, which differ in mucilage content. A combination of biochemical, cytological, and proteomic analyses was used to assess composition and structure. Our analyses revealed that flaxseed mucilage (FM) is predominantly composed hemicellulose (HC) and branched rhamnogalacturonan I (RG-I), with variations in RG-I branching patterns observed between cultivars. Minor constituents, such as homogalacturonan (HG) and rhamnogalacturonan II (RG-II), also contribute to mucilage architecture. Proteomic analysis identified a diverse set of proteins in FM, some of which may be involved in mucilage modification. Differences in mucilage content and composition between Kallfu and Wenutram highlight the structural complexity of FM and its potential functional implications. These findings provide new insights into how variations in FM composition influence its architecture and release properties, advancing the understanding of cell wall structure in relation to mucilage extrusion.